2008
DOI: 10.1143/jjap.47.7428
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy Study on the Location and Distribution of Eu3+ Ions in TiO2 Nanoparticles

Abstract: Eu 3þ -and non-doped TiO 2 nanoparticles were synthesized by the sol-gel method at sintering temperatures of 500 or 900 C. The photoluminescence spectra of these nanoparticles have been investigated at various temperatures between 290 and 12 K. Two kinds of Eu 3þ photoluminescence spectra were observed. One spectrum consists of sharp lines; the other consists of broad bands. The former was obtained by indirect excitation into Eu 3þ with light of wavelengths shorter than 330 nm, while the latter was obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Compared to the reported TiO 2 crystals, [41][42][43] the TiO 2 spheres synthesized in this work yield a larger band gap, which is consistent with the results from Pan and coworkers. 44 The larger band gap observed in our study is attributed to the amorphous phase of the TiO 2 particles, 45 as indicated in the XRD patterns. Thus, the 270 nm broad band absorption most possibly originates from the undoped TiO 2 spheres.…”
Section: Optical Properties and Their Potential Application In Wsupporting
confidence: 54%
“…Compared to the reported TiO 2 crystals, [41][42][43] the TiO 2 spheres synthesized in this work yield a larger band gap, which is consistent with the results from Pan and coworkers. 44 The larger band gap observed in our study is attributed to the amorphous phase of the TiO 2 particles, 45 as indicated in the XRD patterns. Thus, the 270 nm broad band absorption most possibly originates from the undoped TiO 2 spheres.…”
Section: Optical Properties and Their Potential Application In Wsupporting
confidence: 54%
“…On the other hand, substitution of TiO 2 with rare earth elements has recently attracted much attention . Some more studies on the photoluminescent materials based on TiO 2 nanocrystals have been reported as follows.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, substitution of TiO 2 with rare earth elements has recently attracted much attention. [25][26][27][28][29] Some more studies on the photoluminescent materials based on TiO 2 nanocrystals have been reported as follows. Europium (Eu(III))-doped TiO 2 nanocrystals, which were synthesized via Ar/O 2 thermal plasma oxidizing mists of liquid precursors mists of Ti tetra-n-butoxide and Eu(III) nitrate, consisting of mixtures of the anatase (30-36 nm) and rutile (64-83 nm) polymorphs, showed bright red emissions either by exciting the TiO 2 host with UV light shorter than 405 nm or by directly exciting Eu(III) at a wavelength beyond the absorption edge (405 nm) of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have demonstrated that the Eu 3+ dopant is really incorporated within the sub-surface of the titania nanocrystallites. 8,[14][15][16][17][18][19][20] It thus could be used as a probe of the effects of interfacial charge transfer processes at semiconductor interfaces.…”
Section: Introductionmentioning
confidence: 99%